2010
DOI: 10.1111/j.1468-8123.2009.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexation and ion association in hydrothermal fluids: insights from quantum chemistry and molecular dynamics

Abstract: Complexation by ligands in hydrothermal brines is a fundamental step in the transport of metals in the Earth's crust and the formation of ore deposits. Thermodynamic models of mineral solubility require an understanding of metal complexation as a function of pressure, temperature and composition. Over the past 40 years, mineral solubilities and complexation equilibria under hydrothermal conditions have been predicted by extrapolating thermodynamic quantities using equations of state based on the Born model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 80 publications
(150 reference statements)
2
11
0
Order By: Relevance
“…Murakhtina et al (2006) used density functional theory (DFT) based ab initio MD to calculate the H-NMR chemical shift of HCl(aq), and showed good agreement with experimental results. Sulpizi and Sprik (2008;2010) applied ab initio thermodynamic integration by constraining a dummy proton to calculate the free energy of dissociation of a series of acids ('vertical energy gap' technique); they obtained excellent agreement for logKd (57 ºC) values to within 0.4 log units for several small acid molecules (HCl, H2S, formic acid), and within 2 log units for the wide range of acids investigated. They obtained logKd values of 6.7~7.1 for HCl(aq) at 57 ºC (330 K), in excellent agreement with the IUPAC value of 7 at 25 °C (Perrin, 1982).…”
Section: Pka Measurements Via Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Murakhtina et al (2006) used density functional theory (DFT) based ab initio MD to calculate the H-NMR chemical shift of HCl(aq), and showed good agreement with experimental results. Sulpizi and Sprik (2008;2010) applied ab initio thermodynamic integration by constraining a dummy proton to calculate the free energy of dissociation of a series of acids ('vertical energy gap' technique); they obtained excellent agreement for logKd (57 ºC) values to within 0.4 log units for several small acid molecules (HCl, H2S, formic acid), and within 2 log units for the wide range of acids investigated. They obtained logKd values of 6.7~7.1 for HCl(aq) at 57 ºC (330 K), in excellent agreement with the IUPAC value of 7 at 25 °C (Perrin, 1982).…”
Section: Pka Measurements Via Molecular Dynamics Simulationsmentioning
confidence: 99%
“…However, the anomalous Cu enrichment within the Lease granite may be related to the exsolution of an aqueous fluid phase. The mobility and concentration of Cu in hydrothermal fluids is largely a function of the salinity of the aqueous fluid because the solubility of a likely CuCl 2 complex is proportional to the Clconcentration of the fluid [80,81]. As the granites of the Zaaiplaats tin field are thought to have intruded at approximately 4 to 5 km depth, it is very likely that the magmas underwent fluid saturation as evident in the abundant manifestations of magmatic-hydrothermal alteration and mineralization described herein [15,28,82].…”
Section: Discussionmentioning
confidence: 99%
“…The decreasing volume, caused by crystallization, may have led to shrinking of the volume occupied by the magma and partial detachment from the roof, allowing the formation of the marginal pegmatitic zone. The abundance of hematized feldspars, suggests a relatively oxidizing environment, which could have been achieved by fluid mixing or boiling [81,84,85]. Pollard et al [28] showed that these granites evolved in a closed system with little to no external influence, thus oxidation via boiling is the most likely mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entropy is an additional driving force for the ion association due to changes in the local solvent structure near the critical point and above as discussed, e.g., by Sherman (2010) and Mei et al (2014) based on AIMD simulations. The dominant effect arises from the translational entropy through hydration changes of the ions during the aqueous reaction.…”
Section: Thermodynamic Datamentioning
confidence: 99%